Pembentukan Model Log Linier Tiga Dimensi pada Asosiasi Sikap Diskriminatif dan Stigma terhadap Orang dengan HIV/AIDS, Pengetahuan Komprehensif HIV/AIDS dan Tingkat Pendidikan Remaja Perempuan di Indonesia - Rini Rahani; Elma Theana (Jurnal Statistika dan Aplikasinya, 2022)
Reducing Discrimination and negative stigma against people living with HIV/AIDS (PLWHA ) was one of three crucial issues in the "Getting to Zero" policy. Discrimination and negative stigma against PLWHA could be performed by anyone, including teenagers. Female adolescents, compared with male adolescents, were more discriminative toward PLWHA. Comprehensive knowledge of HIV/AIDS was essential in determining discriminatory attitudes and negative stigma. Some previous studies employed comprehensive knowledge of HIV/AIDS as the dependent variable. However, in other studies, it was employed as a determinant of discriminatory attitudes and negative stigma towards PLWHA. This study aimed to accomplish the best model of the relationship between discriminatory attitudes and negative stigma on PLWHA, comprehensive knowledge of HIV/AIDS and education level using a linear log model. This study used data from the 2017 IDHS with female adolescents as the unit of analysis. The results showed that the third order was not significant in the model. Furthermore, backward elimination showed that homogeneous association was the best model for modelling the association of the three research variables.